Doppler ultrasound improves diagnostic accuracy for testicular torsion. (2nd November 2021) - Teurneau-Hermansson, Karl; Zindovic, Igor; Jakobsson, Jon; Navntoft, Anders; Nozohor Ekmark, Ann; Salö, Martin; Wagenius, Magnus
Abstract: Background: Doppler ultrasound can diagnose testicular torsion with high sensitivity and specificity but may delay surgical treatment. This study aims to assess whether the use of doppler ultrasound, in cases with intermediate clinical suspicion of testicular torsion, can improve diagnostic accuracy compared to clinical assessment alone. Methods: We implemented a new clinical algorithm where patients with intermediate suspicion of testicular torsion undergo doppler ultrasound within 60 min. This study compared the patients that presented within one year prior to the implementation (group 1) to the patients who presented within one year after the implementation (group 2). The primary outcome measure was failure to confirm testicular torsion upon surgical exploration (negative surgical exploration). Missed testicular torsion was one of the secondary endpoints. Results: 590 consecutive patients were included. 322 (55%) in group 1 and 268 (45%) in group 2. There were 9 (2.8%) testicular torsions in group 1 vs 9 (3.4%) in group 2 ( p  = 0.69) and 2 (0.6%) missed testicular torsions in group 1 vs 0 in group 2 ( p  = 0.50). Doppler ultrasound was performed in 65 patients (24.2%) in group 2 vs 0 in group 1 ( p  < 0.01). Negative surgical exploration was performed in 27 (8.4%) patients in group 1 vs 8 (3.0%) in group 2 ( p  < 0.01). Conclusion: Doppler ultrasound assessment of patients at intermediate clinical risk of testicular torsion significantly reduced the frequency of negative surgical explorations without increased rate of missed testicular torsions.